The Effect of Hyperbaric Oxygen Therapy on Markers of Oxidative Stress and the Immune Response in Healthy Volunteers - de Wolde, Silke D.; Hulskes, Rick H.; de Jonge, Stijn W.; Hollmann, Markus W.; van Hulst, Robert A.; Weenink, Robert P.; Kox, Matthijs (Frontiers in Physiology, 2022)
Hyperbaric oxygen therapy (HBOT) consists of breathing 100% oxygen under increased ambient pressure. There are indications that HBOT induces oxidative stress and activates immune pathways. However, previous research on immunological effects of HBOT has mainly been established in in vitro experiments and selected patient populations, limiting generalizability and increasing the chances of confounding by comorbidities and specific patient-related factors. More insight into the immunological effects of HBOT would aid investigation and comprehension of potentially novel treatment applications. Therefore, in this study, we investigated the effects of three 110-minute HBOT-sessions with 24-hour intervals on immunological parameters in healthy, young, male volunteers. Blood samples were obtained before and after the first and third HBOT sessions. We assessed neutrophilic reactive oxygen species (ROS) production, systemic oxidative stress (plasma malondialdehyde (MDA) concentrations) as well as neutrophil phagocytic activity, plasma concentrations of tumor necrosis factor (TNF), interleukin (IL)-6, IL-8, and IL-10, and production of TNF, IL-6, and IL-10 by leukocytes ex vivo stimulated with the Toll-like receptor (TLR) ligands lipopolysaccharide [TLR4] and Pam3Cys [TLR2]). We observed decreased neutrophilic ROS production and phagocytosis following the second HBOT session, which persisted after the third session, but no alterations in MDA concentrations. Furthermore, plasma concentrations of the investigated cytokines were unaltered at all time points, and ex vivo cytokine production was largely unaltered over time as well. These results indicate no induction of systemic oxidative stress or a systemic inflammatory response after repeated HBOT in healthy volunteers but may suggest exhaustion of ROS generation capacity and phagocytosis.